Level of Responsiveness of Police Personnel at Police Station VI Batasan Hills Quezon City in Emergency Cases: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Batasan Hills Quezon City reportedly has a high crime rate in 2023. The majority of the peopleliving in Batasan Hills are concerned about their safety. The crimes included are eight indexcrimes; murder, homicide, physical injury, rape, robbery, theft, and motorcycle theft. Accordingto the QCPD, the high crime solution rate can be attributed to three things: the full use ofQCitizen Helpline 122, an improved emergency hotline that offers assistance in times of needas well as a mechanism for callers to complain and provide feedback; the effectiveness of thethree-minute police response time policy through the Integrated Command and ControlCenter; and the ongoing conduct of simulation exercises and constant monitoring of identifiedcrime-pr.The data gathered showed that the respondents are characterized by age, gender, and civilstatus, and all of the respondents were police personnel who are working in Police Station 6Batasan Hills Quezon City. The data gathered shows that the police personnel are responsivewhen needed. The police officers/personnel are also in favor of additional mobile cars toimprove the response of police to take action in emergency situations. The respondents arealso in favor of adding police patrol officers.The result of the study shows that most of the police personnel that were surveyed are men.Police officers/personnel are responsive in order to prevent or lessen the crime in a certainplace. The impact of responsiveness and alertness of the police personnel can lower thecrime rate in Quezon city.
Keywords: Criminology